Serbian diplomacy in deterrence - Blagojević Veljko (Srpska Politička Misao)
Resume Diplomacy represents the first line of promotion and defense of national interests and one of the sources of power, alongside with military, economic, information and other forms of power. The importance and complexity of diplomacy for Serbia in the contemporary international relations are perhaps most evident in terms of deterrence when a major war is being waged on European soil, which will certainly have long-term consequences for the international system. In addition to these factors, the persistent unresolved issues stemming from the Yugoslav heritage, notably the contentious matter of Kosovo and Metohija's status, underscore the imperative for Serbia to consistently harness its full national potential to establish a robust and comprehensive deterrence strategy under the constraints of a policy of military neutrality. This policy, in turn, further compounds the complexity of the challenges at hand. The effectiveness of diplomacy is one of the key prerequisites for successful deterrence, but its synergy with other instruments of foreign policy cannot be reliably realized without the concept of strategic communication. The goal of this paper is, relying on a realistic theoretical foundation, to provide an analysis of diplomatic functions and examine its significance for effective deterrence and the necessity of synchronized action with other foreign policy instruments; instruments that were primarily developed for deterrence but can be utilized differently if diplomacy fails to navigate the security dilemma's failings.